Heated Humidified High-Flow Nasal Cannula Versus Nasal Continuous Positive Airway Pressure for the Facilitation of Extubation in Preterm Neonates with Respiratory Distress - Kalyan Chakravarthy Konda; Leslie Edward Lewis; Y Ramesh Bhat; Jayashree Purkayastha; Shravan Kanaparthi (Mashhad University of Medical Sciences, 2018)
Background: Heated humidified high-flow nasal cannula (HHHFNC) is gaining popularity as an alternative to nasal continuous positive airway pressure (nCPAP) therapy in the management of preterm neonates with respiratory distress due to ease of administration and patient comfort. However, limited evidence is available addressing its risks and benefits. To study the efficacy and safety of HHHFNC in comparison to nCPAP for the facilitation of extubation in preterm neonates (born at 27-34 weeks of gestation) with respiratory distress.Methods: A prospective observational study was conducted, where 64 neonates were assigned either to nCPAP (n=34) or HHHFNC (n=30) groups post-extubation. The primary outcome was treatment failure (defined by pre-specified criteria) requiring a higher modality of respiratory support within 72 hours after extubation.Results: Treatment failure was seen in 36.7% of neonates assigned to the HHHFNC group compared to 14.7% in the nCPAP group (P=0.043). The incidence and severity of nasal trauma were higher in the nCPAP group compared to the HHHFNC group (nCPAP: 58.6% vs. HHHFNC: 15.7%; P=0.001). No significant difference was observed between the two groups in terms of other outcomes such as days on primary non-invasive ventilation (NIV), days of total NIV, duration of hospitalization, days to reach full enteral feeding, weight gain at discharge, incidence and severity of nasal trauma, incidence of pneumothorax, necrotizing enterocolitis, intraventricular hemorrhage, retinopathy of prematurity, sepsis, and death.Conclusion: Though a gentler modality with less incidence of nasal trauma, HHHFNC does not appear to be as effective as nCPAP in the management of preterms with respiratory distress